ANALYSIS OF DIFFERENCES IN PROFIT PERSISTENCE AND ACCOUNTING CONSERVATISM BEFORE THE COVID-19 PANDEMIC AND AFTER THE COVID-19 PANDEMIC (CASE STUDY OF PARATOURISM AND TRANSPORTATION COMPANIES LISTED ON THE IDX PERIOD (2018-2020) - Mega Arum (Jurnal Ekonomi, 2022)
Global conditions are worsening due to the emergence of a new virus that is dangerous and deadly. With conditions that are increasingly declining, causing the company to experience profit gains with fluctuating fluctuations as a result of a decrease in the number of passengers and tourists during the Covid-19 pandemic, this phenomenon can affect the persistence of company profits. So the researchers tried to examine the Analysis of Differences in Profit Persistence and Accounting Conservatism Before the Covid-19 Pandemic and After the Covid-19 Pandemic (Case Study of Tourism and Transportation Companies Registered on the IDX Period (2018-2020). This study used a different test using SPSS. 25. Based on the results of the research and discussion in the previous chapter, regarding the analysis of differences in earnings persistence and accounting conservatism before and after the Covid-19 pandemic, several conclusions can be drawn, including the following: There were significant differences from the presentation of profits before the pandemic covid-19 and after there was a covid-19 pandemic in tourism and transportation companies (H1 accepted). There was no significant difference in accounting conservatism between before there was a covid-19 pandemic and after the covid-19 pandemic in tourism and transportation companies (H2 rejected).